2015
DOI: 10.3892/ijmm.2015.2070
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV ameliorates acute pancreatitis in rats by inhibiting the activation of nuclear factor-κB

Abstract: This study aimed to investigate the effects of astragaloside IV (AS-IV; 3-O-β-D-xylopyranosyl-6-O-β-D-glucopyranosylcycloastragenol), which has been reported to have comprehensive pharmacological functions, on sodium taurocholate (NaTc)/L-arginine (L-Arg)-induced acute pancreatitis (AP) in rats in vivo and in rat pancreatic acinar cells in vitro. NaTc-induced experimental AP was induced in rats by injecting 4% NaTc (0.1 ml/100 g) in the retrograde direction of the biliopancreatic duct. L-Arg-induced experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…AS-IV, the primary pure saponin which is isolated from the root of astragalus membranaceus, was an effective compound with distinct pharmacological effects, including protecting against ischemic brain injury (6), lung inflammation (7), acute pancreatitis (8) and cardiac trauma (9).…”
Section: Introductionmentioning
confidence: 99%
“…AS-IV, the primary pure saponin which is isolated from the root of astragalus membranaceus, was an effective compound with distinct pharmacological effects, including protecting against ischemic brain injury (6), lung inflammation (7), acute pancreatitis (8) and cardiac trauma (9).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported to alleviate pancreatitis by inhibiting NF‐κB signaling. In rat models of AP induced by sodium taurocholate and L‐arginine, it was found to protect from the inflammatory insult in both the models in vivo as well as in vitro in pancreatic acinar cells (Qiu et al , ). Cumulatively, the study indicated that Astragaloside IV acts as an antioxidant and suppresses the progression of pancreatitis by inhibiting the inflammatory signaling.…”
Section: Herbal Remedies Used For Treating Pancreatitismentioning
confidence: 99%
“…Total cellular protein was extracted from cultured cells using lysis buffer, and subjected to western blot analysis as previously described (23). Dilutions of primary antibodies were as follows: BTG2 at a dilution of 1:1,000 (Sigma-Aldrich), Bax at a dilution of 1:1,000 (Abcam, Cambridge, MA, USA) and β-actin at a dilution of 1:10,000 (Abcam).…”
Section: Patientsmentioning
confidence: 99%